Voice or exit? Political corruption and voting intentions in Hungary. Issue 7 (2nd October 2020) - Snegovaya, Maria
ABSTRACT: How does perceived political corruption affect electoral preferences? Scholarship of Eastern Europe addressed this question primarily through the study of observational data. This study contributes to the existing scholarship by addressing the endogeneity problem and allows to causally interpret effects of perceived corruption on voting intentions. It combines hypotheses tested in earlier studies to investigate the impact of perceived political corruption on different electoral choices. A survey experiment in Hungary shows that exposure to political corruption makes respondents more likely to abstain from voting, less likely to support the incumbent party, and more likely to expect the anti-establishment party to win.